Looking Forward, Looking Back: Future Challenges for Narrative Research: An event commemorating the tenth anniversary of the Centre for Narrative Research, University of East London - Andrews, Molly; Brockmeier, Jens; Erben, Michael; Esin, Cigdem; Freeman, Mark; Georgakopoulou, Alexandra; Hydén, Margareta; Hyvärinen, Matti; Jolly, Margaretta; Rustin, Michael; Sagan, Olivia; Squire, Corinne; et al. (Narrative Matters, 2011)
The Centre for Narrative Research was founded at the turn of the millenium. To commemorate its tenth anniversary, we organised an event which took place on November 10, 2010, at the Marx Memorial Library in London. The day had a very flexible format. We began with a few opening words from the three co-directors (Molly Andrews, Corinne Squire, and Maria Tamboukou) and the Research Fellow (Cigdem Esin) of CNR. This was followed by contributions from six leading narrative scholars (Jens Brockmeier, Michael Erben, Mark Freeman, Margareta Hydén, Margaretta Jolly, and Olivia Sagan) to which Alexandra Georgakopoulou and Matti Hyvärinen then responded. Following lunch, the sixty participants were broken up into smaller groups, where they discussed issues raised in the morning session. The day concluded with a final discussion piece offered by Mike Rustin. The six presenters were faced with a formidable challenge. We invited them to write pieces of approximately 500 words on "the promise and challenges for future narrative research, including critiques of and hopes for our own scholarship." These were prepared in advance of the event, and sent to the discussants, who were asked not only to comment upon the set of issues raised, but also to provide a framework for looking at the problems as a whole set. Not only did the contributors and discussants come from a range of different backgrounds and geographical locations, but the range of intellectual interests represented by those who attended the day was very marked: poets, writers of fiction, policy makers, psychoanalysts, sociologists, psychologists, political scientists, social workers, and others. Perhaps the most outstanding feature of the day was the conversations which happened across boundaries, characterised by both a search for common ground as well as a recognition of the different intellectual standpoints represented by the people there. What follows are written versions of the prepared, spoken contributions, which helped to frame the discussion for the day. It is our hope that the stimulating thought pieces prepared for this event can be used as a launch pad for further discussion into the realm of our shared endeavors in narrative scholarship. To listen to recordings of the day, please visit: http://www.uel.ac.uk/cnr/CNRTenthAnniversaryEvents1.htm